Too Proud to Let Go Narcissistic Entitlement as a Barrier to Forgiveness. (article). - Exline, Julie Juola
Narcissistic entitlement impedes forgiveness in ways not captured by other robust predictors (e.g., offence severity, apology, relationship closeness, religiously. Big Five personality factors) as demonstrated in 6 studies. Narcissistic entitlement involves expectations of special treatment and preoccupation with defending one's right. In study 1, entitlement predicted less forgiveness and greater insistence on repayment for a past offense . Complementary results emerged fom study 2, which used hypothetical transgressions, and Study 3, which assessed broad forgiveness dispositions. Study 4 examined associations with the Big Five, and Study 5 extended the findings to a laboratory context. Study 6 demonstrated that entitlement predicted diminished increases the in forgiveness or overtime. Taken together, these results suggest that narcissistic entitlement is a robust, distinct predictor of unforgiveness. -- (from the author).